If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + 4 = 8 Reorder the terms: 4 + 3c = 8 Solving 4 + 3c = 8 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3c = 8 + -4 Combine like terms: 4 + -4 = 0 0 + 3c = 8 + -4 3c = 8 + -4 Combine like terms: 8 + -4 = 4 3c = 4 Divide each side by '3'. c = 1.333333333 Simplifying c = 1.333333333
| -44=log(x) | | 5u^2-41u+42=0 | | 8x=6*16 | | 8x+4=10x+2.80 | | 23.4=w-3.9 | | 2x+(-8)=19 | | (7w+3)(5w^2+6w-2)= | | 4v^2-25v+35=3 | | -24x+54=6y | | -28=6(v-6)-8v | | .67v+.1666=.7777v+-.83333 | | -9=0.45n | | -19m+12=-14m+-8 | | 2(x-5)2+27=x | | 2(x-5)2+9=x | | n-5n-(-n)= | | 12y=64+4y | | 10r-11=8r+19 | | 90=50/x | | x^2+4x-2=-2 | | .60k+.70=.73k+-.40 | | 2(x-5)2+4=x | | .90=50/x | | Y=0.33x+1 | | 4y-18=2y+14 | | (x+5)+22=90 | | 8y-6=6y+20 | | 2x+8=4x+-2 | | 3x(x-4)=(x-10)(x-2) | | 6a^2b+7ab-3b= | | 11t-14=4t+7 | | -0.5x^2+4.5x=0 |